Randomized phase II study to determine the optimal dose of 3-week cycle nab-paclitaxel in patients with metastatic breast cancer. (February 2021) - Tsurutani, Junji; Hara, Fumikata; Kitada, Masahiro; Takahashi, Masato; Kikawa, Yuichiro; Kato, Hiroaki; Sakata, Eiko; Naito, Yoichi; Hasegawa, Yoshie; Saito, Tsuyoshi; Iwasa, Tsutomu; Taira, Naruto; et al.
Abstract: Background: Chemotherapy-induced peripheral neuropathy is commonly observed in patients treated with nanoparticle albumin–bound paclitaxel (nab-PTX). We conducted a multicenter randomized controlled study to evaluate the optimal dose of nab-PTX. Methods: We compared three different doses of q3w nab-PTX (Standard: 260 mg/m 2 [SD260] vs Medium: 220 mg/m 2 [MD220] vs Low: 180 mg/m 2 [LD180]) in patients with HER2-negative metastatic breast cancer (MBC). Primary endpoint was progression-free survival (PFS). Grade 3/4 neuropathy rates in the three doses were estimated using the logistic regression model. The optimal dose was selected in two steps. Initially, if the hazard ratio (HR) for PFS was <0.75 or >1.33, the inferior dose was excluded, and we proceeded with the non-inferior dose. Then, if the estimated incidence rate of grade 3/4 neurotoxicity exceeded 10%, that dose was also excluded. Results: One hundred forty-one patients were randomly assigned to SD260 (n = 47), MD220 (n = 46), and LD180 (n = 48) groups, and their median PFS was 6.66, 7.34, and 6.82 months, respectively. The HRs were 0.73 (95% confidence interval [CI]: 0.42–1.28) in MD220 vs SD260, 0.77 (95% CI 0.47–1.28) in LD180 vs SD260, and 0.96 (95% CI 0.56–1.66) in LD180 vs MD220. SD260 was inferior to MD220 and was excluded. The estimated incidence rate of grade 3/4 neurotoxicity was 29.5% in SD260, 14.0% in MD220, and 5.9% in LD180. The final selected dose was LD180. Conclusions: Intravenous administration of low-dose nab-PTX at 180 mg/m 2 q3w may be the optimal therapy with meaningful efficacy and favorable toxicity in patients with MBC. Highlights: Nab-Paclitaxel at 260 mg/m 2 is used to treat metastatic breast cancer (MBC). Nab-Paclitaxel frequently causes severe neuropathy or myalgia. A reduced nab-paclitaxel dose of 180 mg/m 2 q3w was effective and had less toxicities. Therapeutic indices of reduced doses were increased compared to the standard dose.